Hormonal responses during two different concurrent-training trials in youth elite soccer players: Does changing the organization of training impact the hormonal response to concurrent exercise? - Enright, K.; Morton, J.; Iga, J.; Drust, B. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: There are no data describing the acute hormonal responses to concurrent-training programmes in youth elite soccer players. Therefore, the aim of this study was to describe the total testosterone (T), cortisol (C), and growth hormone (hGH) responses during two same-day concurrent-training (CT) trials in elite soccer players. METHODS: Thirteen youth elite players (age: 17.0±0.2 years; height, 1.80±0.07 m; body mass, 73.1±5.7 kg; VO2max, 64.4±4.8 mL/kg/min) from an English premier league soccer club completed two CT trials. "Trial 1" (CT1); E (10.30 a.m.) followed by S (02.00 p.m.) and Trial 2 (CT2); strength-training (S) 09.00 a.m. followed by a soccer-specific endurance-training session (E) at 10.30 a.m. Venous blood samples were collected at 5 time-points around training and food intake (T1; 08.00 a.m., T2; 09.45h, T3; 12.30h, T4; 01.45 p.m. and T5; 03.15 p.m.) and analyzed for T (nmol/L) and C (nmol/L) and hGH (ug/L). RESULTS: There was no main effects found between exercise conditions for any hormones (T; P=0.22, C; P=0.07, hGH; P=0.21). Effect size analysis revealed a moderate effect for T at T3 (ES=0.63, CT1; 18.4±3.8, CT2; 15.7±4.7 nmol/L). A moderate effect for T Area Under the Curve (AUC) was observed between conditions (CT1; 300±76 versus CT2; 244±81 [AU]; ES=0.71). A moderate effect was apparent for C concentrations T4 in (ES=-0.95, CT1; 230±69, CT2; 314±105 nmol/L). Moderate effect sizes were observed at T3 and T4 (ES=0.82, CT1; 1.28±1.17, CT2; 0.47±0.75, ES=0.72, CT1; 0.11±0.05, CT2; 0.07±0.06 ug/L-1 respectively). A moderate effect for hGH AUC was observed between trials (CT1; 14±11 versus CT2; 5±9; [AU], ES=-1.08). CONCLUSIONS: The organisation of the concurrent-training protocols used in this study has a negligible impact upon the acute T, C and hGH in youth elite soccer players.